On the value of liquid-air and Pumped-Thermal Electricity Storage systems in low-carbon electricity systems - Georgiou,S; Aunedi,M; Strbac,G; Markides,CN (Energy, 2020)
We consider two medium-to-large scale thermomechanical electricity storage technologies currently under development, namely ‘Liquid-Air Energy Storage’ (LAES) and ‘Pumped-Thermal Electricity Storage’ (PTES). Consistent thermodynamic models and costing methods based on a unified methodology for the two systems from previous work are presented and used with the objective of integrating the characteristics of the technologies into a whole-electricity system assessment model and assessing their system-level value in various scenarios for system decarbonization. It is found that the value of storage depends on the cumulative installed capacity of storage in the system, with storage technologies providing greater marginal benefits at low penetrations. The system value of PTES was found to be slightly higher than that of LAES, driven by a higher storage duration and efficiency, although these results must be seen in light of the uncertainty in the (as yet, not demonstrated) performance of key PTES components, namely the reciprocating-piston compressors and expanders. At the same time, PTES was also found to have a higher power capital cost. The results indicate that the complexity of the decarbonization challenge makes it difficult to identify clearly a ‘best’ technology and suggest that the uptake of either technology can provide significant system-level benefits.